The role of teachers’ social competence in ELT - Saudagar, Ferdiaz (Indonesian Educational Administration and Leadership Journal (IDEAL), 2019)
The teacher’s social competence is one of the four competencies that a professional teacher should have as stated in the Indonesian Government’s Act No.14 in 2005 about teachers in Indonesia. It covers the teacher’s skills in building an effective interaction and communication with their colleagues, students, together with their guardians. In relation to this regulation, language teachers, including the teachers of English, have greater potential to develop an effective communication. In some cases, several problems in communication between teachers of English and their students occur during the inside and outside classroom learning activities. This paper tries to focus on what should language teachers do to build the effective communication with their students based on the perspectives from some field of studies. Finally, this paper also provides some general suggestions and considerations for language teachers, especially the teachers of English to build the effective communication to their students at any situation.